2007
DOI: 10.1002/tox.20249
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic from the marine environment with antimicrobial fouling activity

Abstract: The degradation in performance of submerged marine structures through their colonization by micro- and macrobiota is well known. Historically, toxic surface coatings have been used to control both types of fouling. Legislative requirements worldwide now require alternative non- or minimally toxic coatings to be used. Here we report on the potential for synthetic 2-pentyl-4-quinolinol (PQ), an antibiotic from an Alteromonas sp., as a candidate antifoulant. Hundred micromolar PQ reduces the growth of four marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Of all five tested quinolones (Figure ), HHQ and NHQ had lower IC 50 concentrations than those of their functionalised homologues (HHQ=1.2–4.9 μ m ; NHQ=0.16–1.38 μ m ), which illustrates that in diatoms non‐functionalised quinolones are more potent than that of their functionalised analogues. Although previous studies have shown the toxic effects of HHQ on the coccolithophore E. huxleyi and of PHQ on other diatoms, this study builds on previous findings by testing a broader range of quinolones with structural variations. These experiments not only show that diatom growth is inhibited by a wide range of quinolones, but also that some appear to be considerably more potent than that of PHQ.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Of all five tested quinolones (Figure ), HHQ and NHQ had lower IC 50 concentrations than those of their functionalised homologues (HHQ=1.2–4.9 μ m ; NHQ=0.16–1.38 μ m ), which illustrates that in diatoms non‐functionalised quinolones are more potent than that of their functionalised analogues. Although previous studies have shown the toxic effects of HHQ on the coccolithophore E. huxleyi and of PHQ on other diatoms, this study builds on previous findings by testing a broader range of quinolones with structural variations. These experiments not only show that diatom growth is inhibited by a wide range of quinolones, but also that some appear to be considerably more potent than that of PHQ.…”
Section: Discussionmentioning
confidence: 57%
“…The same compound was also found to inhibit growth and/or motility of the benthic diatoms Amphora coffeaeformis , Navicula sp. and Auricula sp . However, very few other alkylquinolones have been tested on diatoms, despite the diversity of alkylquinolones produced by marine bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…strain Y excreted heat-labile algicidal substance(s) which lyze cells of Gymnodinium catenatum, Chattonella marina, and Heterosigma akashiwo. Recently, Wigglesworth-Cooksey et al [14] demonstrated that synthetic 2-n-pentyl-4-quinolinol, an antibiotic from an Alteromonas sp. reduces the growth of four marine diatoms that usually grow as biofilms and suggested that it has potential as a candidate antifoulant.…”
Section: Discussionmentioning
confidence: 98%
“…and Pseudoalteromonas sp. strain A1-J11 Wigglesworth-Cooksey et al 2007). More specifically, PQ has also been shown to inhibit growth, adhesion and motility of three diatoms in species-specific way, acting on the adhesion mechanisms of each algae type.…”
Section: Quinolonementioning
confidence: 98%
“…Therefore, the application of quinolone derivates would result in the alteration of calcium signal transduction and the deregulation of cellular functions such as the inhibition of respiration, motility, DNA and proteins synthesis, finally leading to algal cell lysis and death (Long et al 2003;Wigglesworth-Cooksey et al 2007) .…”
Section: Quinolonementioning
confidence: 99%